2020
DOI: 10.1080/0284186x.2020.1730437
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and malignant transformation of glottic precursor lesions in Denmark

Abstract: Objectives: Glottic precursor lesion (GPL) is a well-known premalignant condition, but the existing knowledge of incidence and malignant potential is based on subpopulation studies. In this first nationwide study we report data from all verified cases of GPL in Denmark during a 10-year period with focus on incidence and malignant transformation of GPL.Methods: Patients were identified by a search for GPL in the time period from 01.01.2000 to 31.12.2009 using the Danish Pathology Data Base, Patobank, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A total of 18 articles with 3243 participants were included in the final systematic review, and all of these were included in the meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Study characteristics are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 18 articles with 3243 participants were included in the final systematic review, and all of these were included in the meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Study characteristics are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…With regard to time to malignant transformation, only 7 of the included studies provided data for this outcome. 21,24,26,28,31,32,34 These studies were combined to calculate the weighted mean time to transformation, which was determined to be 28.8 months (range, 22.0-35.6 months) for all dysplasia grades.…”
Section: Rate and Time Of Malignant Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] A study by Sannino et al demonstrated that rates of progression to carcinoma for mild and moderate grades of laryngeal dysplasia were 7.7 per cent and 19.8 per cent, respectively. 15 This raised concerns that the treatment and need for follow up of the newly termed 'low-grade lesions' would be crudely underestimated.…”
Section: Introductionmentioning
confidence: 99%